TINJAUAN PUSTAKA TERHADAP HARMONISASI REGULASI DI INDONESIA PASCA-PEMBERLAKUAN METODE OMNIBUS LAW DALAM PENYUSUNAN UNDANG-UNDANG - Gunawan Widjaja (JOURNAL OF LAW AND NATION, 2025)
This study aims to examine regulatory harmonisation in Indonesia after the enactment of the Omnibus Law method in lawmaking through a literature review. The legislative process in Indonesia has faced various problems such as overlap, conflict, and inconsistency between regulations, which have resulted in legal uncertainty and investment barriers. With the implementation of the Omnibus Law method, the government seeks to simplify and consolidate many cross-sector regulations into a single legislative package to create better legal coordination and enhance national competitiveness. The results of the study indicate that the Omnibus Law can promote efficiency, accelerate harmonisation, and clarify the national legal framework. However, on the other hand, its implementation still faces challenges in the form of minimal public participation, transparency issues, and problems of compatibility with Indonesia's civil law system. Therefore, continuous evaluation, institutional strengthening, and the involvement of all stakeholders are needed to ensure the effectiveness and sustainability of regulatory harmonisation through the Omnibus Law.